Nonverbal Communication as a Communication Strategy in Hotel Job Interview: A Narrative Inquiry Study - Luh Eka Susanti; Muhamad Nova (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
Nonverbal communication is portrayed as a communication strategy to convey interpersonal communication meaning. This study aimed at identifying the types of nonverbal communication applied by the job applicant in a hotel job interview and the users’ perspective toward the nonverbal communication applied as a communication strategy. This study employed a qualitative study with narrative inquiry design by interviewing one experienced human resources officer and 2 human resources managers. The data were gathered through interviews in different sections with different informants. The interview was recorded and transcripted. The interview transcription was analyzed to identify the tendency of the informant’s answers. The result showed that the most nonverbal communication occurring in hotel job interview include body language, voice tone, and grooming. The human resources managers and staffs, as an interviewer, prefer to have good attitude over good knowledge. This implied that hotel job applicants must be aware on their body language, voice tone, and grooming before attending a job interview.